Linking Pornography Consumption Motivations to Intention to Engage in Infidelity among Indonesian Young Adults - Yundianto, Devie; Indriani, Wini; Khatami, Muhammad; Mutia Anindita, Siti; Maharani, Winda (Journal of Educational, Health and Community Psychology, 2025)
Infidelity is a global relational problem that can seriously undermine individual and couple well-being. However, limited research has examined how specific motivations for pornography consumption—emotional avoidance, sexual curiosity, excitement seeking, and sexual pleasure—relate to intentions to engage in infidelity. This study aimed to investigate the direct effects of these four dimensions of pornography consumption on intention to engage in infidelity. A total of 159 individuals aged 18–40 years (M = 19.58, SD = 1.43) participated in the study and completed the Pornography Consumption Inventory and the Intention to Infidelity Scale. The analysis showed that emotional avoidance, sexual curiosity, and sexual pleasure were not significantly associated with intention to engage in infidelity. In contrast, the excitement-seeking dimension demonstrated a small but significant positive association with infidelity intention. These findings suggest that pornography consumption, particularly when motivated by excitement seeking, may shape cognitive precursors to infidelity. This study clarifies the dynamic mechanisms linking pornography-related motivations and infidelity intention and offers insight into how individuals may establish psychological boundaries when confronted with opportunities for extradyadic involvement.